Image zooming model based on fractional-order partial differential equation. (2nd January 2017) - Gao, Ran; Gu, Cong; Li, Xiao
Abstract: This paper proposes a new image zooming model based on the fractional-order partial differential equation, which adopts the idea of total variation. The simulation results show that the new model can keep the characteristics of image edge better than the fourth order partial differential equation model since it can retain more texture details. The numerical results shows that the proposed model is effective and practical on image zooming.